RESTORASI EKOSISTEM MANGROVE PADA MEDIA BIODEGRADABLE DI PESISIR DESA WAAI: Restoration Of Mangrove Ecosystem On Biodegradable Media On The Coast Of Waai Village - Gino V Limmon; Eelco Waardenburg; Wouter Lengkeek; Peter Vodegel; Krisye; Yunita A Noya (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mangroves are plants that live on the coast and are affected by sea tides. Mangroves play an important role in estuary areas, namely the border between seawater and fresh water because they have ecological, economic and chemical functions to support the life of organisms. Mangrove ecosystems can experience threats from both natural and human factors. Human activities that cause damage to mangroves are due to a lack of public awareness regarding the importance of mangrove ecosystems for organisms. This is the condition that occurs in the mangrove ecosystem in Waai Village, therefore, it is necessary to restore the mangrove ecosystem. Mangrove ecosystem restoration uses one of the potential media, namely BESE-Element, which is a biodegradable material. Community service is carried out in collaboration with the Pattimura University Maritime Center and Wardenburg Ecology International. The community service activities were carried out for two days, 7-8 February 2023. The result of the activity was that mangrove ecosystem restoration was carried out in semi-enclosed areas using 10 BESE-Element. The types of mangrove species planted were Sonneratia alba, Rhizophora stylosa, and Ceriops tagal. Around BESE-Elements planted seedlings and mangrove propagules as a control for mangroves in BESE-Elements. This restoration activity seems to be applicable not only in Waai Village but also in other areas that have experienced degradation of the mangrove ecosystem.